FREQUENCY OF HEPATIC STEATOSIS IN A RADIOLOGY CLINIC IN PALMAS - Dias Filho, David Ailton; Martins Reis Júnior, Paulo; Andraus, Wellington (Revista de Patologia do Tocantins, 2018)
Introduction: Recent studies suggest that hepatic steatosis is a worldwide distribution pathology that can progress to chronic liver disease with a highly unfavorable outcome resulting in the need for liver transplantation. That’s why early diagnosis is important. The liver biopsy’s considered a "gold standard" in its diagnosis, but the use of ultrasonography helps to detect steatosis in a non-invasive manner and is a very accessible method for the population. Objectives: To evaluate the frequency of steatosis in patients treated at a radiological clinic in Palmas using abdominal ultrasonography; observing its distribution in genders and age groups and its difference between 2010 and 2016. Methods: It was used ultrasound reports of abdomen of 3.222 patients made in 2010 and of 2.346 patients made in 2016. A longitudinal analysis was performed, between these two years, regarding the frequency of hepatic steatosis at the people and also between the genders and the age groups. Results: In 2010, 25,67% of people had hepatic steatosis in the ultrasound report, while in 2016 were 31,67%. In 2010, of the total number of people with steatosis, 52,48% were women and 47,52% were men; however in 2016, 51,94% were women and 48,06% were men. Regarding the age groups, in both periods, as in men and in women, steatosis was lower at the extremes of age and more frequent around the 5th to 7th decades of life. Discussion: The frequency of hepatic steatosis has increased in the period from 2010 to 2016. It was, as seen in the literature, quite high in the 5th and 6th decades of life, besides being more frequent in females. Unlike 2010, in 2016 begins to have children under 20 with signs of steatosis. Conclusion: In the year 2010 the frequency of hepatic steatosis was 25,67%, whereas in 2016 it was 31,84%.